Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1002/ijc.10628
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of apoptosis in human breast cancer cells: Role in tumor progression to the metastatic state

Abstract: Reduction in apoptosis has been associated with tumor metastases and response to chemotherapy in breast cancer. We examine the influence of apoptosis status and the expression of antiapoptotic proteins Bcl-2 and Bcl-x L on metastatic progression and response to therapy in an experimental model of breast cancer. We used human breast cancer cells (MDA-MB 435, MDA-MB 468 and MCF-7) to induce orthotopic xenograft tumors in nude mice. The overexpression of Bcl-2 or Bcl-x L influenced tumorigenicity, 468 transfectan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 56 publications
(28 reference statements)
2
47
0
Order By: Relevance
“…However, multiple studies demonstrated an association of an invasive phenotype of breast cancer cells with suppressed apoptosis [3][4][5]. Similar inverse correlations between invasiveness and the ability to produce an apoptotic response after cell injury were described in prostate cancer [30], colon cancer [31,32], melanoma [33], hepatocellular carcinoma [34] and other types of neoplasia.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…However, multiple studies demonstrated an association of an invasive phenotype of breast cancer cells with suppressed apoptosis [3][4][5]. Similar inverse correlations between invasiveness and the ability to produce an apoptotic response after cell injury were described in prostate cancer [30], colon cancer [31,32], melanoma [33], hepatocellular carcinoma [34] and other types of neoplasia.…”
Section: Discussionmentioning
confidence: 59%
“…Commonly, invasive carcinomas have less apoptosis and are more resistant to chemotherapy [3][4][5]. Several studies showed decreased apoptosis in breast cancer cells in association with cancer progression, invasiveness and metastases [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In metastatic human breast tumor cell lines, overexpression of Bcl-xL can increase cell survival in the vasculature and enhance the formation of distant metastases (Rubio et al, 2001;Fernandez et al, 2002). Likewise, coexpression of Bcl-2 with E1a and activated Ras enhances survival of tumorigenic mouse embryo fibroblasts in the vasculature (Nikiforov et al, 1997).…”
mentioning
confidence: 99%
“…11 In this study, lentiviral vectors were used to deliver the ADRBK1 si-RNA to MDA-MB-231 cells, which is among the best choice currently available for delivering and stably expressing si-RNA in target cells. Lentiviral vectors tend to integrate distally from promoters in introns and thereby limit the oncogenicity, and they are capable of transducing nondividing cells and specifically target the nucleus.…”
Section: Discussionmentioning
confidence: 99%